Epigenetic regulation in myocardial infarction: Non-coding RNAs and exosomal non-coding RNAs - Fadaei, Sara; Zarepour, Fatemeh; Parvaresh, Mehrnoosh; Motamedzadeh, Alireza; Tamehri Zadeh, Seyed Saeed; Sheida, Amirhossein; Shabani, Mohammad; Hamblin, Michael R.; Rezaee, Mehdi; Zarei, Maryam; Mirzaei, Hamed (Frontiers in Cardiovascular Medicine, 2022)
Myocardial infarction (MI) is one of the leading causes of deaths globally. The early diagnosis of MI lowers the rate of subsequent complications and maximizes the benefits of cardiovascular interventions. Many efforts have been made to explore new therapeutic targets for MI, and the therapeutic potential of non-coding RNAs (ncRNAs) is one good example. NcRNAs are a group of RNAs with many different subgroups, but they are not translated into proteins. MicroRNAs (miRNAs) are the most studied type of ncRNAs, and have been found to regulate several pathological processes in MI, including cardiomyocyte inflammation, apoptosis, angiogenesis, and fibrosis. These processes can also be modulated by circular RNAs and long ncRNAs via different mechanisms. However, the regulatory role of ncRNAs and their underlying mechanisms in MI are underexplored. Exosomes play a crucial role in communication between cells, and can affect both homeostasis and disease conditions. Exosomal ncRNAs have been shown to affect many biological functions. Tissue-specific changes in exosomal ncRNAs contribute to aging, tissue dysfunction, and human diseases. Here we provide a comprehensive review of recent findings on epigenetic changes in cardiovascular diseases as well as the role of ncRNAs and exosomal ncRNAs in MI, focusing on their function, diagnostic and prognostic significance.